Examining perceived adolescent socioemotional development and repeated camp experiences using a planned missing data design. (19th October 2020) - Gagnon, Ryan J.
Abstract: In questionnaire-based research, leisure investigators must balance the need for comprehensive measurement with participant fatigue associated with lengthy questionnaires. Planned missing data designs (PMDD) offer a solution to reduce survey length while maintaining precision in measurement. This study introduces PMDD through an examination of the influence of parental years of camp experience as a child ( M = 2.54 years) and their child's level of camp experience ( M = 1.39 years) on parental perceptions of developmental outcomes (PPDO) associated with camp participation. Data were collected from a cross-sectional sample of 699 parents via an online survey examining the influence of repeated camp experiences on adolescent socioemotional development following their child's ( M age = 12.25 years) participation in a residential summer camp experience. Utilizing a structural equation model in combination with the PMDD, the results indicated neither parent nor child level of camp experience influenced PPDO score.